Meta Analisis Pengaruh Model Problem Based Learning Terhadap Kemampuan Berpikir Kritis Siswa - Agnezi, Laura Aliyah (Universitas Negeri Padang, 2020)
From the results of the meta-analysis in this study it was concluded that the model of peoblem based learning was very influential on students at the high school, vocational and junior high school levels. The effect of the lowest influence is found at the level of PT education. Overall the problem based learning model has an influence in improving students' critical thinking skills. From the calculation of the effect size using the Glass comparison formula and the derived formula, an average effect size of 1.23 is generated with a large category. The price shows that the application of the problem based learning model plays a major role in improving students' critical thinking sk